Uji Rendemen Nira dan Gula Semut Aren (Arenga pinnata Merr.) Hasil Penyadapan Pagi dan Sore Hari dengan Instrumen Refraktometer - Maghfirah, Inayatul; Santoso, Hari; Syauqi, Ahmad (Jurnal SAINS ALAMI (Known Nature), 2019)
Enau (sugar palm) trees are multi-use plants and almost all parts of the plant can be used for human needs. The nira of sugar palm (legen or saguer) can be processed into palm sugar. The purpose of this study was to measure rendemen nira and palm sugar from the results of tapping in the morning and evening. The research method uses survey by measuring the pH and volume of nira that obtained in the morning and evening and directly processing it into palm sugar. The results of the study showed the morning tapping,  temperature =  , the rendemen of palm sugar = 11.50% and the water content of palm sugar = 4.05%. In the evening tapping,   temperature = , pH nira of palm sugar = 6,3, the rendemen of palm sugar = 11.48% and the water content of palm sugar = 3.57%. The results of the t-test pairs analysis were obtained P temperature = 0.041 ˃ 0.025, P pH  nira of sugar palm = 0.134 ˃ 0.025, P brix nira of sugar palm = 0.557 ˃ 0.025, P rendemen of palm sugar = 0.975 ˃ 0.025 and P water content of palm sugar = 0.975 0.025. There were no significant difference from nira of palm sugar produced by tapping morning and evening. ABSTRAKPohon Enau (Aren) tanaman multi guna dan hampir semua bagian tanaman dapat dimanfaatkan untuk keperluan manusia. Nira aren (legen atau saguer) dapat diolah menjadi gula semut. Tujuan penelitian ini untuk mengukur rendemen nira dan rendemen gula semut dari hasil penyadapan pagi dan sore hari. Metoda penelitian menggunakan survey dengan mengukur pH dan volume nira yang didapat pagi hari dan sore hari serta langsung mengolahnya menjadi gula semut. Hasil penelitian menunjukkan pada penyadapan pagi hari ,   ,  rendemen gula semut = 11,50 % dan kadar air gula semut = 4,05%. Pada penyadapan sore hari ,   ,  rendemen gula semut = 11,48 % dan kadar air gula semut = 3,57%. Hasil analisis uji t-Test Pairs diperoleh P suhu = 0,041 ˃ 0,025, P pH nira aren = 0,134 ˃ 0,025, P brix nira aren= 0,557 ˃ 0,025, P rendemen gula semut = 0,975 ˃ 0,025 dan P kadar air gula semut = 0,975 ˃ 0,025. Tidak ada perbedaan yang nyata dari nira aren hasil penyadapan pagi dan sore hari.Kata kunci: Rendemen, Nira, Aren, Gula semut